Mechanism of enhanced Na-K-ATPase activity in cortical collecting duct from rats with nephrotic syndrome. - Féraille, E (1993)
The maximal hydrolytic activity of Na-K-ATPase is specifically increased in the cortical collecting duct (CCD) of rats with puromycin-induced nephrotic syndrome (NS). This stimulation is independent of aldosterone and of endogenous ouabain-like substance. To investigate the mechanism responsible for this change, we compared the maximal Na-K-ATPase hydrolytic activity, the ouabain sensitive 86Rb influx, the specific [3H]ouabain binding, and the sensitivity of Na-K-ATPase to ouabain in the CCD of control rats and of rats given an intraperitoneal injection of puromycin 7 d before study. Both Na-K-ATPase activity and ouabain-sensitive 86Rb influx increased two-fold in rats with NS (ATPase activity: 34.1 +/- 2.1 vs. 18.0 +/- 0.7 pmol.mm-1 x min-1 +/- SE, n = 6, P < 0.001; Rb influx: 14.4 +/- 0.7 vs. 7.4 +/- 0.4 peq.min-1 +/- SE, n = 6, P < 0.001) whereas specific [3H]ouabain binding decreased in rats with NS (6.9 +/- 0.7 vs. 9.0 +/- 0.6 fmol.mm-1 +/- SE, n = 6, P < 0.005). Therefore, the maximal turnover rate of Na-K-ATPase increased over twofold in rats with NS (5,053 +/- 361 vs. 2,043 +/- 124 cycles.min-1 +/- SE, n = 6, P < 0.001). Analysis of the curves of inhibition of Na-K-ATPase by ouabain showed the presence of two Na-K-ATPase populations in both control and NS rats: a highly sensitive population (apparent Ki: 1.4 x 10(-6) M and 0.9 x 10(-6) M) and a less sensitive moiety (apparent Ki: 2.6 x 10(-4) M and 1.1 x 10(-4) M). The enhancement of Na-K-ATPase activity observed in the CCD of rats with NS was entirely due to the stimulation of the population of Na-K-ATPase with low ouabain sensitivity. These results suggest that a dysregulation of this subclass of Na-K-ATPase might be the primary cause of sodium retention in this model of nephrotic syndrome.